Syntactic bootstrapping attitude verbs despite impoverished morphosyntax. (2nd January 2022) - Huang, Nick; White, Aaron Steven; Liao, Chia-Hsuan; Hacquard, Valentine; Lidz, Jeffrey
ABSTRACT: Attitude verbs like think and want describe mental states (belief and desire) that lack reliable physical correlates that could help children learn their meanings. Nevertheless, children succeed in doing so. For this reason, attitude verbs have been a parade case for syntactic bootstrapping. We assess a recent syntactic bootstrapping hypothesis, in which children assign belief semantics to verbs whose complement clauses morphosyntactically resemble the declarative main clauses of their language, while assigning desire semantics to verbs whose complement clauses do not. This hypothesis, building on the cross-linguistic generalization that belief complements have the morphosyntactic hallmarks of declarative main clauses, has been elaborated for languages with relatively rich morphosyntax. This article looks at Mandarin Chinese, whose null arguments and impoverished morphology mean that the differences necessary for syntactic bootstrapping might be much harder to detect. Our corpus analysis, however, shows that Mandarin belief complements have the profile of declarative main clauses, while desire complements do not. We also show that a computational implementation of this hypothesis can learn the right semantic contrasts between Mandarin and English belief and desire verbs, using morphosyntactic features in child-ambient speech. These results provide novel cross-linguistic support for this syntactic bootstrapping hypothesis.